REINFORCEMENT DALAM PEMBELAJARAN KARAKTER SANTRI MELALUI MANAJEMEN BIMBINGAN DAN KONSELING ISLAM - Ach. Sofauzzad; Eka Varida Kusuma (Jurnal Psikotes, 2025)
The important value of character education is the wisdom of differences in values and cultures in social life to create a nation's civilization. To achieve this goal, the education system in schools has developed 3 subsystems, consisting of the administration subsystem, the instruction subsystem and the student assistance or coaching subsystem (personal services for students). The field of guidance and counseling is one of the aspects in providing assistance/coaching to students. The development of educational character can be realized through the management of Islamic guidance and counseling. Related to the concept of management, the application or implementation of guidance and counseling management is one of the manifestations of a planned activity on how to organize guidance and counseling activities, optimize the human resources in the guidance and counseling organization to achieve goals, monitor the implementation of guidance and counseling activities, and evaluate the results of guidance and counseling activities. With the existence of Islamic guidance and counseling management, educational goals can be achieved, especially in strengthening the character of students.